2008
DOI: 10.2119/2007-00134.vardanian
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mediators of Liver Ischemia and Reperfusion Injury: A Brief Review

Abstract: Ischemia and reperfusion injury is a dynamic process that involves multiple organ systems in various clinical states including transplantation, trauma, and surgery. Research into this field has identified key molecular and signaling players that mediate, modulate, or augment cellular, tissue, and organ injury during this disease process. Further elucidation of the molecular mechanisms should provide the rationale to identify much-needed novel therapeutic options to prevent or ameliorate organ damage due to isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
88
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 121 publications
2
88
0
Order By: Relevance
“…I/R injury induces an inflammatory response and cytokine release from non-parenchymal cells and passenger leucocytes in the liver (Fondevila et al 2003;Montalvo-Jave et al 2008;Teoh and Farrell 2003). The distal cascade of the inflammatory response following I/R which leads to organ damage has been studied extensively (Clavien et al 2001;Jaeschke 2003;Jaeschke and Lemasters 2003;Vardanian et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…I/R injury induces an inflammatory response and cytokine release from non-parenchymal cells and passenger leucocytes in the liver (Fondevila et al 2003;Montalvo-Jave et al 2008;Teoh and Farrell 2003). The distal cascade of the inflammatory response following I/R which leads to organ damage has been studied extensively (Clavien et al 2001;Jaeschke 2003;Jaeschke and Lemasters 2003;Vardanian et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The liver exhibits both direct cellular damage as the result of the ischemic insult as well as further dysfunction and damage resulting from activation of inflammatory pathways (10). We have previously shown that hepatocytes actively release HMGB1 in response to oxidative stress, suggesting that these parenchymal cells can provide danger signals to neighboring immune cells in the liver to promote inflammation and organ damage (11).…”
mentioning
confidence: 99%
“…Activation of Kupffer cells with production of reactive oxygen species, upregulation of the inducible nitric oxide synthase and proinflammatory cytokines, and neutrophil accumulation contribute to inflammation-associated liver damage. [1][2][3][4] One may therefore speculate whether a reduction in leukocyte adhesion and transmigration into the interstitium may reduce the incidence and severity of I/R-induced complications. FTY720 (2-amino-2-[4-octylphenyl]-1,3-propaneldiol hydrochloride), a synthetic structural analogon of sphingosine related to myriocin, is considered to be a possible drug targeting this problem.…”
mentioning
confidence: 99%